2018
DOI: 10.1002/app.47229
|View full text |Cite
|
Sign up to set email alerts
|

Curing properties of high‐Ortho phenol‐formaldehyde resins with co‐catalysis

Abstract: In this study, sodium carbonate (Na 2 CO 3 ) was used as a catalyst to prepare high-ortho phenol-formaldehyde (HOPF) resin, and ester and carbonate curing accelerators were used to increase its curing rate. The physicochemical properties of the prepared resins and the mechanism of curing acceleration were investigated. The results showed that, with the addition of Na 2 CO 3 , the ortho/para ratio of methylol groups increased from 7.257 to 27.800. The gel time of the cure-accelerated HOPF resins decreased from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…The challenges faced when manufacturing a polymer‐matrix composite lie, not only, in the uniform dispersion of the filler but also in the strength of the adhesion between the filler and the matrix 24 . The improvement of the interfacial region enables efficient stress transfer between the two components of the composite.…”
Section: Introductionmentioning
confidence: 99%
“…The challenges faced when manufacturing a polymer‐matrix composite lie, not only, in the uniform dispersion of the filler but also in the strength of the adhesion between the filler and the matrix 24 . The improvement of the interfacial region enables efficient stress transfer between the two components of the composite.…”
Section: Introductionmentioning
confidence: 99%
“…The NH characteristic peak of HBPA was located at 2.36 ppm (peak 4). [ 28 ] The above findings indicated that the HBPA had been successfully synthesized. In the spectrum of HBPA–g–WSSPS, the typical NH signal appeared shifted to 2.65 ppm (peak 2), indicating that the HBPA was grafted onto the WSSPS, thereby providing a hyperbranched polysaccharide.…”
Section: Resultsmentioning
confidence: 92%
“…[ 23–25 ] Over the past few years, tremendous approaches have been proposed for increasing the dispersibility and interfacial interaction in polymer matrix through functionalizing GO. [ 26–31 ] Sahu and his coworkers [ 26 ] used poly (allyl amine) to functionalize GO (GO‐ g ‐PAA), and with the addition of 0.7 wt% GO‐ g ‐PAA, the critical stress intensity factor (K IC ) and bending strength of epoxy composite were increased by 87 and 43%, respectively. Wan et al [ 31 ] achieved modified GO with 3‐glycidoxypropyltrimethoxysilane (silane‐f‐GO), which improved the interfacial and mechanical properties of epoxy composites.…”
Section: Introductionmentioning
confidence: 99%